2016
DOI: 10.1155/2016/2394957
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Ganglion Cell Atrophy in Homonymous Hemianopia due to Acquired Occipital Lesions Observed Using Cirrus High-Definition-OCT

Abstract: Purpose. To report a reduction in macular ganglion cell layer and inner plexiform layer (GCL+IPL) thickness and circumpapillary retinal nerve fiber layer (cpRNFL) thickness using spectral-domain optical coherence tomography in patients with homonymous hemianopia due to posterior cerebral artery (PCA) stroke. Methods. Seven patients with PCA stroke were examined using Cirrus high-definition-OCT. The GCL+IPL thicknesses were divided into the hemianopic and unaffected sides. The relationship between the time afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 23 publications
4
29
0
1
Order By: Relevance
“…In these SD-OCT studies, inner retinal thinning was observed in both the peripapillary and macular areas, in accordance with the patients' hemianopic visual field defects. [9][10][11][12][13][14][15][16][17][18] More recently, sweptsource OCT (SS-OCT), which permits even faster scanning, has been used to study inner retinal thinning in homonymous hemianopia. 19 Recent advancements in spectral-domain optical coherence tomography (SD-OCT) has enabled the assessment of the RGC layer and the ganglion cell complex (GCC), which includes the retinal layers from the internal limiting membrane to the inner plexiform layer.…”
Section: Introductionmentioning
confidence: 99%
“…In these SD-OCT studies, inner retinal thinning was observed in both the peripapillary and macular areas, in accordance with the patients' hemianopic visual field defects. [9][10][11][12][13][14][15][16][17][18] More recently, sweptsource OCT (SS-OCT), which permits even faster scanning, has been used to study inner retinal thinning in homonymous hemianopia. 19 Recent advancements in spectral-domain optical coherence tomography (SD-OCT) has enabled the assessment of the RGC layer and the ganglion cell complex (GCC), which includes the retinal layers from the internal limiting membrane to the inner plexiform layer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that retinal thinning possibly due to RTSD is present in humans, as determined using OCT in patients with HVFDs due to lesions not involving the optic tract and LGN. 8–10,24,25 In our previous study, we reported that the inner retina corresponding to the blind visual fields demonstrated thinning within a few years after the onset of occipital damage using spectral-domain OCT. 9 Some of the patients who developed a post-geniculate lesion within 1 year of evaluation did not show inner macular thinning by OCT. 26 Meier et al found that the retinal nerve fibre layer of a patient with HVFD due to an occipital lobe abscess was thinned but no RAPD was noted after 2 years. 10 Conversely, small RAPD due to HVFDs has been detected immediately after stroke, when no retinal atrophy should be present.…”
Section: Discussionmentioning
confidence: 99%
“…GCL + IPL has been established as a sensitive marker of retinal thinning from acquired damage to the posterior visual pathways 3, 4, 5, 6, 7, 8, 9, 10. This is intuitive, as half of all RGCs exist within the fovea and are responsible for central vision.…”
Section: Discussionmentioning
confidence: 99%
“…Several distributions of retinal thinning have been described corresponding with homonymous hemianopia or homonymous quadrantanopsia1, 2, 3, 4, 5, 6, 7, 8 , 10 ; however, to our knowledge fewer studies have examined the relatively rare case of isolated macular-involving scotoma from injury to the occipital tip 9 . We describe this pattern of RNFL and retinal ganglion cell (RGC) complex loss from retrograde trans-synaptic neuronal degeneration.…”
Section: Introductionmentioning
confidence: 99%